2016
DOI: 10.5455/medarh.2016.70.116-118
|View full text |Cite
|
Sign up to set email alerts
|

Restless Legs Syndrome in Patients with Hypertension and Diabetes Mellitus

Abstract: Aim:The aim of this study was to analyze frequency of restless legs syndrome (RLS) in patients with hypertension and diabetes mellitus.Patients and Methods:It was analyzed 120 subjects (from Health Center Živinice/Family Medicine Department) through a survey conducted in the period from March to June 2015, of which 30 (8 men/22 women). Subjects were 30 patients with longtime hypertension (HT)(18 men/12 women), 30 patients with diabetes mellitus (DM) type I or II (9 men/21 women), 30 patients with long standing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
1
7
2
Order By: Relevance
“…Previous studies from other countries found lower rates of RLS among patients with diabetes [22][23]. A previous study showed no association of restless legs syndrome with type 2 diabetes in contradiction to the current findings [24]. The different rates of RLS may be explained by other comorbidities and study types [25].…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies from other countries found lower rates of RLS among patients with diabetes [22][23]. A previous study showed no association of restless legs syndrome with type 2 diabetes in contradiction to the current findings [24]. The different rates of RLS may be explained by other comorbidities and study types [25].…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, diabetic patients reported high prevalence of RLS (22.8%), and this is confirmative with other studies conducted in Iran (19.5%),[8] Bosnia and Herzegovina (21%),[13] the United States (24.5%),[5] Brazil (27%),[11] and Turkey (28.3%). [6] This result supports the study findings of other studies[1314161718] that sleep disorders correlate highly with hypertension and diabetic population in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Iron deficiency is a well-known condition correlating with several forms of symptomatic RLS in the diabetic population; our study was in consistent with a previously reported study that showed an association between RLS and iron status in diabetic patients. [19] The association between RLS and hypertension and heart diseases could be due to the effects of a prolonged sleep loss in increasing the probability of developing hypertension and diabetes,[1314161718] which may lead to vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies from other countries found lower rates of RLS among patients with diabetes [22,23]. A previous study [24] showed no association of the restless leg syndrome with type 2 diabetes in contradiction to the current findings. The different rates of RLS may be explained by other comorbidities and study type [25].…”
Section: The Relationship Of the Restless Syndrome (No=26) To Sex Necontrasting
confidence: 99%